Preferred Interpersonal Distances: A Global Comparison. (May 2017) - Sorokowska, Agnieszka; Sorokowski, Piotr; Hilpert, Peter; Cantarero, Katarzyna; Frackowiak, Tomasz; Ahmadi, Khodabakhsh; Alghraibeh, Ahmad M.; Aryeetey, Richmond; Bertoni, Anna; Bettache, Karim; Blumen, Sheyla; Błażejewska, Marta; et al.
Human spatial behavior has been the focus of hundreds of previous research studies. However, the conclusions and generalizability of previous studies on interpersonal distance preferences were limited by some important methodological and sampling issues. The objective of the present study was to compare preferred interpersonal distances across the world and to overcome the problems observed in previous studies. We present an extensive analysis of interpersonal distances over a large data set ( N = 8, 943 participants from 42 countries). We attempted to relate the preferred social, personal, and intimate distances observed in each country to a set of individual characteristics of the participants, and some attributes of their cultures. Our study indicates that individual characteristics (age and gender) influence interpersonal space preferences and that some variation in results can be explained by temperature in a given region. We also present objective values of preferred interpersonal distances in different regions, which might be used as a reference data point in future studies.